2015
DOI: 10.1126/science.aaa0472
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency solution-processed perovskite solar cells with millimeter-scale grains

Abstract: State-of-the-art photovoltaics use high-purity, large-area, wafer-scale single-crystalline semiconductors grown by sophisticated, high-temperature crystal growth processes. We demonstrate a solution-based hot-casting technique to grow continuous, pinhole-free thin films of organometallic perovskites with millimeter-scale crystalline grains. We fabricated planar solar cells with efficiencies approaching 18%, with little cell-to-cell variability. The devices show hysteresis-free photovoltaic response, which had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

103
2,525
8
17

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 3,095 publications
(2,653 citation statements)
references
References 58 publications
103
2,525
8
17
Order By: Relevance
“…In addition, average grain size as a function of processing temperature in this hot‐casting method and traditional annealing method are shown in Figure 4d. It is demonstrated that grain size of the as‐prepared perovskite layer is larger and reaches the order of magnitude of millimeter with increasing substrate temperature along with incorporation of DMF and NMP, which results in a very high PCE of 18% after device fabrication 34. Notably, this work is consistent with the study by Xu et al that MACl plays a critical role in enhancing crystallization quality of perovskite layer 12…”
Section: Perovskite Layersupporting
confidence: 90%
“…In addition, average grain size as a function of processing temperature in this hot‐casting method and traditional annealing method are shown in Figure 4d. It is demonstrated that grain size of the as‐prepared perovskite layer is larger and reaches the order of magnitude of millimeter with increasing substrate temperature along with incorporation of DMF and NMP, which results in a very high PCE of 18% after device fabrication 34. Notably, this work is consistent with the study by Xu et al that MACl plays a critical role in enhancing crystallization quality of perovskite layer 12…”
Section: Perovskite Layersupporting
confidence: 90%
“…Perovskite solar cells have emerged as competitive solution‐processed candidates for photovoltaic applications due to the demonstration of high power conversion efficiency (PCE), ease of fabrication, and low materials cost 1, 2, 3, 4, 5, 6, 7, 8, 9. The efficiency of perovskite solar cells has rapidly risen from 3.8% to over 22.1% just within the past several years 10, 11.…”
mentioning
confidence: 99%
“…The grain size increases fast to ≈1 μm in a 25 min annealing process. It has been reported that the big grain size CH 3 NH 3 PbI 3− x Br x has less inner grain boundaries, which is benefited for reduction of charge recombination 34, 35. The EDX mapping result shows that “Au,” “Br,” and “I” elements are homogeneously distributed in the meso‐Al 2 O 3 layer (Figure 2b), reflecting a good evidence of the existence of Au NPs and CH 3 NH 3 PbI 3− x Br x materials.…”
Section: Resultsmentioning
confidence: 99%